Exploratory Study on Occupational Health Hazards among Health Care Workers in the Philippines - Erwin Martinez Faller (Ubiquity Press, 2018)
Background and Purpose: Healthcare workers are prone to occupational hazards. The study aims to identify the occupational health hazards among healthcare workers in the Philippines and its essential relevant developmental framework. This article evolved on the responses of participants on how they can improve strategies and barriers for healthcare workers to comply with Occupational Health and Safety (OSH). Methods: A qualitative study design in which 15 healthcare workers from nurses (4), pharmacists (3), medical technologies (4) and medical doctors (4) participated: two focus group of three to four participants each and eight in-depth interviews. The thematic sessions were identified, including occupational health and safety policy implementations, hazards experiences, barriers, and strategies for quality improvement for OSH. Focus groups and interviews using transcript-based analysis were identified relating to emerging themes on the challenges they had experienced while accessing provisions of OSH in their workplace. Results: Majority of the participants revealed the existence of policy on Occupational Health and Safety (provisions, guidelines and regulations on OHS from the government) and mentioned that there were limited OHS officers to supervise the healthcare workers in their workplace. Some have limited accessibility to the requirements of the implementation of OHS (free facemasks, gloves, disinfectants, machines, OSH staff, etc.) among healthcare workers, while the workload of the staff in the implementation of OHS in the workplace gradually increased. The results indicated that the respondents were knowledgeable in the implementation of OHS in the workplace, and that there was no existing ASEAN framework on the protection and promotion of the rights of healthcare workers in their workplace. Facilities need to improve health assessment, and to ensure constant evaluation of the existing laws for healthcare workers (quality assurance of existing policies) in their working areas. Direct access to OSH officers, occupational hazards education, emergency contact etc. must be improved. Adherence must be strengthened to fully comply with the OHS standards. Conclusion: The researchers inferred that issues and concerns regarding compliance on provisions of occupational health and safety among health care workers must be properly addressed through immediate monitoring and reevaluation of personnel in terms of their knowledge and practices in OHS. Barriers and challenges have been identified in the study that can lead to improved compliance among healthcare workers in regards to OHS.